Studies and Synthesis of Substituted 4-Biphenyl Acetamide Derivatives - Khullar, Anju (Asian Journal of Chemistry, 2019)
A new series of substituted 4-biphenylamides have been synthesized by condensation of 4-biphenyl acetic acid with different primary amines (aromatic and aliphatic). 4-Biphenyl acetic acid was first treated with thionyl chloride in dry benzene to prepare substituted 4-biphenyl acetyl chloride, which is then treated with different aliphatic or aromatic amines to synthesize various substituted 4-biphenyl acid-amide derivatives. The structure of newly synthesized compounds has been established by analytical and spectral methods. These synthesized compounds have shown antifungal properties against Fusarium udum and Curvularia lunata.